Eksistensi Dan Keabsahan Surat Keputusan Bersama 3 Menteri Tentang Penjatuhan Sanksi Terhadap Pegawai Negeri Sipil - Ridwan Ridwan (Fakultas Hukum Universitas Islam Indonesia, 2021)
This study analyzes the Joint Ministerial Decree (SKB) of 3 Ministers on the imposition of sanctions against Civil Servants (PNS) who commit criminal acts of occupational crimes or crimes related to their positions. This is a normative research, with a statutory approach and conceptual approach. The results of this study conclude that this SKB is a policy regulation that becomes a guideline for Civil Service Officers in imposing sanctions on civil servants. This SKB is in accordance with legal principles, does not contradict statutory regulations, and does not violate AUPB, unless if it is enforced retroacively.